1996
DOI: 10.1016/0014-5793(96)00188-3
|View full text |Cite
|
Sign up to set email alerts
|

Activities associated with the presence of ribosome‐inactivating proteins increase in senescent and stressed leaves

Abstract: The ribosome-inactivating proteins (RIPs) from Hura crepitans and Phytolaeca americana release adenine from herring sperm DNA. Leaf extracts from these plants show the same enzymatic activities as the RIPs. The translation inhibitory activity and the activity on DNA are both increased in the leaves of both plants during senescence or when subjected to heat or osmotic stress. It is proposed that a physiological role of RIPs could be to intervene in the death of plant cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 26 publications
2
58
1
1
Order By: Relevance
“…RIPs were found to be peculiar N-glycosidases, and to remove a single adenine from a precise position in rRNA (A 4324 in the case of rat liver ribosomes) (review in [13]). More recently, however, it was reported that some, but not all, RIPs remove more than one adenine residue per ribosome [14], and that saporins [15,16] and other RIPs ( [12]; unpublished results by Barbieri et al) remove adenine from RNA other than rRNA and also from DNA. Consistently, ricin removes 2'-deoxyadenine from a synthetic dodecanucleotide with a GdA-GA loop, actually at a faster rate than it removes adenine from a similar dodecanucleotide with a GAGA loop [17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RIPs were found to be peculiar N-glycosidases, and to remove a single adenine from a precise position in rRNA (A 4324 in the case of rat liver ribosomes) (review in [13]). More recently, however, it was reported that some, but not all, RIPs remove more than one adenine residue per ribosome [14], and that saporins [15,16] and other RIPs ( [12]; unpublished results by Barbieri et al) remove adenine from RNA other than rRNA and also from DNA. Consistently, ricin removes 2'-deoxyadenine from a synthetic dodecanucleotide with a GdA-GA loop, actually at a faster rate than it removes adenine from a similar dodecanucleotide with a GAGA loop [17].…”
Section: Resultsmentioning
confidence: 99%
“…Unless otherwise stated, polynucleotide:adenosine glycosidase activity was determined by measuring adenine released from various substrates by HPLC [10] essentially following the procedure of [11] as described by [12]. Reactions were run for 40 rain at 30°C in a final volume of 50 I.tl containing 50 mM Na-acetate, pH 4.0, 100 mM KCI and RIP and substrate as indicated in the legends to the appropriate figures.…”
Section: Determination Of Enzyme Activitiesmentioning
confidence: 99%
“…The possibility that depurination is caused by a host of minor contaminants seems unlikely, since : (i) the saporin-L1 protein is apparently highly purified (see the Experimental section), (ii) enzymic activity is still present at very low protein concentrations, (iii) the effect on protein synthesis and DNA depurination varies in the same direction in RIP-containing leaves ( [14] ; F. Stirpe, L. Barbieri, P. Gorini, P. Valbonesi, P. Bolognesi and L. Polito, unpublished work), (iv) all RIPs, including recombinant ones (L. Barbieri, P. Valbonesi, P. Gorini, A. Bolognesi and F. Stirpe, unpublished work), show activity towards hsDNA, and (v) to our knowledge, no other known enzyme has this activity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, preliminary results showed that some saporins released adenine from all RNAs tested, and also from poly(A) and DNA, but did not affect ribomononucleotides, thus being actually polynucleotide :adenosine glycosidases [13]. Finally, two isoforms of PAP, PAP from seeds (PAP-S) and an RIP from Hura crepitans, release adenine from DNA [14].…”
Section: Introductionmentioning
confidence: 96%
“…Such a RIP-mediated regulation of gene expression may explain why some RIPs, such as JIP60 [30] and IRIP (W. J. Peumans, B. Hause and E. J. M. Van Damme, unpublished work), are (partly) located in the nucleus. Moreover, gene inactivation by RIPs may also explain why in many cases the synthesis of RIPs is closely associated with senescence [9,31]. Though these presumed regulatory activities are still speculative, they can explain some biological activities of RIPs that definitely do not rely on their RNA N-glycosidae or PAG activity.…”
Section: Discussionmentioning
confidence: 99%